Giardia sp. and Cryptosporidium sp. in Iberian Wolf - Pereira, Ana Luísa; Mateus, Teresa Letra; Llaneza, Luis; Duarte, Sofia (Journal of the Hellenic Veterinary Medical Society, 2019)
[Abstract]: A subsample consisting of fifty fecal samples from wild Iberian Wolf (Canis lupus signatus), from the northwest of Spain were collected in the field. The samples were analyzed for cysts of Giardia sp. and oocysts of Cryptosporidium sp. using a direct immunofluorescence antibody test (IFA). Giardia sp. and Cryptosporidium sp. were found in 20.0 % of the samples examined. Simple infections were more frequent (90.0 %) with seven (14.0 %) positive for Giardia sp. and two (4.0 %) positive for Cryptosporidium sp. To the authors’ knowledge, this is the first report of occurrence of Cryptosporidium sp. in Iberian Wolf. This study was financially supported by Escola Universitária Vasco da Gama, Coimbra, Portugal, and for that, the authors are grateful. The authors are also thankful to the Regional Government of Galicia and the Spanish Ministry of Agriculture, Food and Envi-ronment that financed the wolf census and authorized the faecal samples collection.